NEFAs Influence the Inflammatory and Insulin Signaling Pathways Through TLR4 in Primary Calf Hepatocytes in vitro - Deng, Qinghua; Du, Liyin; Zhang, Yuming; Liu, Guowen (Frontiers in Veterinary Science, 2021)
Dairy cows are often in a state of negative energy balance, because of decreased dry matter intake and increased energy requirements, initiating lipid mobilization and leading to high serum β-hydroxybutyrate and nonesterified fatty acid levels, which can induce ketosis and fatty liver in dairy cows. We all have known that inflammation and insulin resistance are also common diseases in perinatal period of dairy cows. So what is the relationship between negative energy balance, insulin resistance and inflammation in dairy cow? In order to study the role of NEFAs in the NF-κB inflammatory and insulin signaling pathways through TLR4, we cultured bovine primary hepatocytes and added different concentrations of NEFAs to test the mRNA and protein levels of inflammatory and insulin signaling pathways. Our experiments indicated that NEFAs could activate the NF-κB inflammatory signaling pathway and influence insulin resistance through TLR4. However, an inhibitor of TLR4 alleviated the inhibitory effects of NEFAs on the insulin pathway. In conclusion, all of these results indicate that high-dose NEFAs can activate the TLR4/NF-κB inflammatory signaling pathway, and reduce the sensitivity of the insulin pathway through the TLR4/PI3K/AKT metabolic axis.